1999
DOI: 10.1002/j.2050-0416.1999.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Fusarium Mycotoxins on Growth of Brewing Yeasts. 2. Deoxynivalenol and Nivalenol*

Abstract: Tlte effect of the trichothecene mycotoxins deoxynivalenol (DON) and nivalenol (NIV) on growth of Saccharomyces cerevisiae lager and ale strains has been studied. Tlte toxins were added into tlte growth medium in low and high concentrations. Yeast growth was assessed by measurement of dry iveight or relative growth, cell number, viability and conductance change of the growth medium using direct and indirect methods. Tlte inhibitory effect of both DON and NIV on yeast growth was dependent on toxin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Flannigan et al 62 observed similar results when ZEN was present at 5-50 µg g -1 , DAS at 5-10 µg g - 1 210 , and DON at 50 µg g -1 176 . Whitehead and Flannigan 210 reported no effect with DON at levels of 20 µg g -1 , while Boeira et al 12 found no effect of NIV at concentrations less than 50 µg g -1 on strains of lager and ale yeasts. In a more recent study, the combined interactions of DON, ZEN and fumonisin B 1 on yeast were observed 12 .…”
Section: Mycotoxins In Cerealsmentioning
confidence: 98%
See 1 more Smart Citation
“…Flannigan et al 62 observed similar results when ZEN was present at 5-50 µg g -1 , DAS at 5-10 µg g - 1 210 , and DON at 50 µg g -1 176 . Whitehead and Flannigan 210 reported no effect with DON at levels of 20 µg g -1 , while Boeira et al 12 found no effect of NIV at concentrations less than 50 µg g -1 on strains of lager and ale yeasts. In a more recent study, the combined interactions of DON, ZEN and fumonisin B 1 on yeast were observed 12 .…”
Section: Mycotoxins In Cerealsmentioning
confidence: 98%
“…Whitehead and Flannigan 210 reported no effect with DON at levels of 20 µg g -1 , while Boeira et al 12 found no effect of NIV at concentrations less than 50 µg g -1 on strains of lager and ale yeasts. In a more recent study, the combined interactions of DON, ZEN and fumonisin B 1 on yeast were observed 12 . A synergistic interaction between DON and ZEN was noted, but only at very high concentrations.…”
Section: Mycotoxins In Cerealsmentioning
confidence: 98%
“…The toxicogenic effects of DON and related mycotoxins are well established for animals and humans (for a review, see reference 165), leading to the adoption of strict quality standards for DON in malt. In addition to potentially threatening human health, high concentrations of these mycotoxins have been shown to inhibit yeast growth during beer fermentation (166,167).…”
Section: Barleymentioning
confidence: 99%
“…It was found that Fusarium-contaminated wheat with a high concentration of DON (3.95 mg kg −1 ) negatively affected the fermentation by S. cerevisiae process and reduced the ethanol concentration by 13.5% in the fermented wort ( Figure 5). The explanation for the decrease in the ratio of fermentation by S. cerevisiae might be the inhibitory effect of high concentrations of Fusarium mycotoxins on yeast growth [147]. Whitehead and Flannigan [148] suggested that trichothecenes inhibit mitochondrial function, causing slower oxygen utilisation by the yeast resulting in a slower growth rate.…”
Section: Impact Of Enzymes On Alcohol Fermentation Of Mycotoxin Contamentioning
confidence: 99%